Severe thrombocytopaenia in a patient after acute myocardial infarction with influenza - Barwinek, Katarzyna; Dziurzyńska, Joanna; Błaszczyk, Aleksandra (Nursing Problems / Problemy Pielęgniarstwa, 2023)
This paper presents the case of 59-year-old patient who presented to the clinic with weakness, shortness of breath at rest, fever, and dry cough. Based on laboratory tests and physical examination, the patient was diagnosed with pneumonia. On the third day of hospitalization the patient presented resting, burning pain in the chest. Electrocardiogram (ECG) showed signs of STEMI. The percutaneous coronary intervention (PCI) attempt was not therapeutically successful, and the patient received heparin. Progressive thrombocytopaenia was found after myocardial infarction. Based on this, an assumption of heparin-induced thrombocytopaenia was made. Any clinical suspicion of heparin-induced thrombocytopaenia requires that treatment should not be withheld pending the result. This paper pays attention to this problem.